HUKUM DAN LINGUISTIK FORENSIK - Rusdiansyah Rusdiansyah (Al-Amwal : Journal of Islamic Economic Law, 2020)
Legal cases that occur in social life today not only occur in real life, but many of them occur in cyberspace, in this case social media. The aims of this paper is to determine the relationship and contribution of forensic linguistics to law. The legal case can be analyzed based on the speech used. Forensic linguistics exists as one of the tools in the judiciary to assist in reviewing the speech that arises with the context of the speech that occurs. so, the task of linguists in this case lingus is very necessary in analyzing things that are in this linguistic aspect. A linguist can not determine guilty or not or also determine the punishment to the perpetrators, but a linguist can provide evidence of language related to the case.